ISSUANCE OF GREEN BOND FOR SUSTAINABLE DEVELOPMENT OF PEATLANDS - Naradipatya Pratanjana; Gumanti Oloan Simbolon (Sociae Polites, 2020)
Peatlands, with their important role, are in need of great attention, both from the government and also environmentalists. The role of corporations is really needed and is expected to be able to accelerate the improvement of the quality of peatlands, so that the benefits are maintained. Issuance of Green Bond is expected to be able to encourage the achievement of this goal. It is hoped that companies operating in and around the Peatland area will be able to create sustainable Peatland development efforts. The synergy between companies and green investors is expected to be an aspect of improving the economy, both for companies, investors and the public. Companies as publishers have an increasingly large role in maintaining the balance of peatlands. Benefits in the form of incentives from the Financial Services Authority (OJK) will also be obtained by companies that issue green bonds. Investors, especially green investors who are interested in environmental issues will have new investment alternatives. The emergence of a development program initiated by the company, of course, will also have an impact on society, in the form of the withdrawal of a number of workers, as well as the increase in other economic activities as a result of the increase in the standard of living of the community. Keywords: Green Bond, Peatland